Glutamic Acid Decarboxylase in Spores of Bacillus megaterium and Its Possible Involvement in Spore Germination - Foerster, Charlene Wehe (1973)
Spores of Bacillus megaterium were examined for glutamic acid decarboxylase (GAD). Although dormant spores showed no GAD activity, spores given sonic treatment and heat-activated spores had high activities when assayed for this enzyme. Several parameters of GAD in heat-activated spores were examined. The effects of KCN, NaN(3), 2,4-dinitrophenol, and KF on GAD activity were examined. Only KCN was an effective inhibitor of GAD activity in heated spores and was also shown to be the only effective inhibitor of GAD activity in vegetative bacteria. Similar patterns of inhibition were obtained with GAD activity and with spore germination, KCN being the only effective inhibitor of both, although at different concentrations. Spore GAD activity in heat-activated spores showed a loss with storage at 4 C; on the other hand, storage at 25 C was not accompanied by a loss, but, to the contrary, showed an increase in GAD activity of about 30%. A comparison of GAD activity at different times during germination, growth, and sporulation showed it to be highest in freshly germinated spores. Although vegetative cells contained GAD activity, the level in log-phase cells was approximately one-half the level obtained with freshly germinated spores. Heat-activated mutant spores with a requirement of γ-aminobutyric acid for germination gave no GAD activity. GAD activity appeared in mutant spores after germination and increased to levels comparable to parent spores after 9 min of germination.